Effect of stressful conditions on the carotenogenic activity of a Colombian strain of Dunaliella salina (2019)
The objective was evaluate the carotenogenic activity ofDunaliella salinaisolated from the artificial saltflats of municipality of Manaure (Department of La Guajira, Colombia). Two experimental testings weredesigned, in triplicate, to induce the reversibility of the cell tonality depending on the culture conditions.In the first test (A), to induce the reversibility from green to red tonality inD. salinacells, these were cul-tured in J/1 medium at a concentration of 4.0 M NaCl, 390mmol m 2s 1, 0.50 mM KNO3. In the second test(B), to induce the reversibility from red to green cell tonality, the cultures were maintained in J/1 medium1 M NaCl, 190mmol m 2s 1, 5.0 mM KNO3and pH 8.2. The population growth was evaluated by cell countand the pigment content was performed by spectrophotometric techniques. It was found that in both teststhe culture conditions influenced the population growth and the pigments production ofD. salina. Therewas a significant difference between the mean values of total carotenoids in the test A with 9.67 ± 0.19lg/ml and second test with 1.54 ± 0.08lg/ml at a significance level of p < 0.05. It was demonstrated thatthe culture conditions of test A induce the production of lipophilic antioxidants, among these carotenoids.The knowledge of the stressful conditions for the production of carotenoids fromD. salinaisolated fromartificial saline of Manaure opens a field in implementation of this biotic resource for biotechnological pur-poses, production of new antibiotics, nutraceuticals and/or biofuels production.